SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/146649-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asphaltene Nanoscience on Understanding Oilfield Reservoirs

Abstract: Understanding asphaltene gradients and dynamics of fluids in reservoirs had been greatly hindered by the lack of knowledge of asphaltene nanoscience. Gravitational segregation effects on oil composition, so important in reservoir fluids, are unresolvable without knowledge of (asphaltene) particle size in crude oils. Recently, the "modified Yen model" also known as the Yen-Mullins model, has been proposed describing the dominant forms of asphaltenes in crude oils: molecules, nanoaggregates and clusters. This as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The island architecture exhibits attractive forces in the molecule interior (PAH) and steric repulsion from alkane peripheral groups. These structures were also observed in oil reservoirs with extensive vertical offset, where gravitational effects are evident (Creek et al, 2010;Mullins et al, 2011). Results from analytical methods such as time-resolved fluorescence depolarization (TRFD) (Groenzin & Mullins, 2000), Nuclear magnetic diffusion (Freed et al, 2007); Fluorescence correlation spectroscopy (FCS) (Andrews et al, 2006), DC conductivity (Zeng et al, 2009;Goual et al, 2011) indicate that the size of asphaltene molecules is  1.5 nm.…”
Section: Structure and Role Of Resinsmentioning
confidence: 97%
“…The island architecture exhibits attractive forces in the molecule interior (PAH) and steric repulsion from alkane peripheral groups. These structures were also observed in oil reservoirs with extensive vertical offset, where gravitational effects are evident (Creek et al, 2010;Mullins et al, 2011). Results from analytical methods such as time-resolved fluorescence depolarization (TRFD) (Groenzin & Mullins, 2000), Nuclear magnetic diffusion (Freed et al, 2007); Fluorescence correlation spectroscopy (FCS) (Andrews et al, 2006), DC conductivity (Zeng et al, 2009;Goual et al, 2011) indicate that the size of asphaltene molecules is  1.5 nm.…”
Section: Structure and Role Of Resinsmentioning
confidence: 97%
“…Nevertheless, the physicochemical properties of EHO such as low API gravity and high contents of heavy components such as resins and asphaltenes lead to high viscosities through the formation of a complex viscoelastic network [4] and generate substantial technological challenges for production, transporting and refining operations [5][6][7]. The crude oil heavy fractions, particularly the asphaltenes, are high dipole moment compounds [8] due to its chemical structure which is composed by a polyaromatic core surrounded by aliphatic chains and may contain heteroatoms such as oxygen, nitrogen, and sulfur [9,10]. The high polarity caused by this chemical structure generates in this compounds a self-association characteristic, leading to the asphaltene arrangement in aggregates that, depending on their sizes, can be classified as nanoaggregates or clusters [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to that, it seems justifiable to consider most of the oil and gas production technologies, reservoir treatments and stimulation as nanotechnologies (Evdokimov et al, 2006;Mullins et al, 2011). Several studies have shown that asphaltene precipitation as a side effect of some EOR processes, mostly miscible gas injection, hinders the oil production from the wells.…”
Section: Nanostructure Of Asphaltenic Componentsmentioning
confidence: 99%